Development Of An Effective Composition Of Thickening Agents (Progress Annals: Journal of Progressive Research, 2023)
A composition has been developed for printing mixed fabrics based on cotton and nitron fibers. The coloristic characteristics of printed fabrics have been studied. It has been established that the developed thickener composition gives the printing ink sufficient adhesiveness, viscosity, plasticity and other properties, makes it possible to obtain a soft, elastic, transparent, uniform and firmly fixed film on the fabric, and does not reduce the brightness of the color.